ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze the factors that influence capital structure. Such factors are profitability (ROA), the structure of assets (tangibility), sales growth, firm size, and likuidity (CR) either through parsial to capital structure at company Indeks LQ 45 which enlisted in BEI. Period of research started from year of  2010-2012 (3 year). This study uses secondary data sources of the data derived by the Indonesia Stock Exchange with a tree year study period. Sampling was purposive sampling method. Data analysis using classic assumption test, multiple linear regression analysis, coefficient of determination, F test and t test, profitability (ROA), the structure of assets (tangibility), sales growth, firm size, likuidity (CR), as independent variabels and capital structure as dependent variabel. The results showed that profitability (ROA), the structure of assets (tangibility), and sales growth negative and significantly affect the capital structure so the hypothesis is rejected, likuidity (CR) negative and significantly affect the capital structure so the hypothesis is rejected. firm size affect the capital structure so the hypothesis is accepted.Keywords: Capital Structure, Profitability, The Structure of Assets, Sales Growth, Firm Size, Likuidity